Liberalization and Protectionism: an Analysis of Experience Application in Different Countries of the World (Economics and region, 2021)
The authors analyze the use of liberalization and protectionism elements in different countries of the world and at different stages of their development. Protectionism and liberalization are two alternative directions of the state's trade policy. In today's world practice, neither protectionist nor liberal trade policy is used in its purest form. Each country uses elements of both trade policy options, combining them according to its economic goals at this stage, the situation in the world and national economies. The purpose of the article is to analyze the peculiarities of liberalization and protectionism application in different countries of the world and to prove the feasibility of combining them in the implementation of the country's foreign trade policy. An analysis of the experience of many countries in the world shows that complete liberalization is not always appropriate and does not always contribute to the country's economic growth. In the middle of the last century, protectionism dominated in trade policy in most countries of the world. But the situation changed dramatically in the second half of the last century. The tendency towards liberalization of goods and services exchange and openness of national markets has emerged and continues to strengthen in the world economy.The authors investigate the features of using the tools of protectionism and liberalization in the leading countries of the world. A retrospective analysis shows that countries which are  the benchmarks for the liberals now – the US, the UK, and at a later stage – Japan, Germany, Finland, South Korea, Taiwan and other successful states – have not used free trade and free investment policies until they crossed defined boundary of economic development. Particular attention is paid to the so-called regional trade agreements, the number of which has been growing rapidly in recent decades. The authors emphasize that the trade-political regimes of regional groups can be classified as a system of collective protectionism, which is a kind of "hybrid" of protectionism and free trade. Thus, current realities show that without the use of protectionist tools, many participants in international trade cannot do. The rules governing the use of these instruments are subject to dozens of agreements that are part of the WTO legal package. As a rule, states try to pursue a balanced foreign trade policy using flexible protectionist methods while maintaining free trade elements in order to create a favorable climate in economic relations with other countries.
Keywords: liberalization; protectionism; international trade; trade barriers; free trade